Kreativitas Keterampilan Seni Rupa Peserta Didik Di Kelas Salak di TK Pembina 1 Medan - Feby Alvia Purba; Intanni Sari; Chronika Febrianti; Elya Siska Anggraini (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Fine arts education in kindergarten (TK) has an important role in developing students' creativity and fine arts skills. This research aims to describe the creativity of students' fine arts skills in the Salak class at Kindergarten Pembina 1 Medan. The research method used is qualitative with observation, interview and documentation techniques. The results of the research show that students in the Salak class have different levels of creativity in fine arts skills. This can be seen from the diversity of their fine art works, both in terms of shape, color and techniques used. Factors that influence the creativity of students' fine arts skills include interest, talent and stimulus provided by the teacher. Teachers need to provide appropriate stimulus that is appropriate to the students' level of development so that they can develop their creativity and fine arts skills optimally.